Design of a motorised plasma delivery system for ultra-precision large optical fabrication. (2nd September 2020) - Zhou, Hui; Bennett, Adam; Castelli, Marco; Jourdain, Renaud; Guo, Jiang; Yu, Nan
Abstract: A unique plasma figuring (PF) process was created and demonstrated at Cranfield University for manufacturing extremely large telescopes. The atmospheric pressure processing is faster and more cost-effective than other finishing processes; thus, providing an important alternative for large optical surfaces. The industrial scale manufacturing of thousands of ultra-precision metre-scale optics requires a robust PF machine: this requirement is achieved by making the plasma delivery system (PDS) performance repeatable. In this study, a dedicated PDS for large optical manufacturing was proposed to meet the industrial requirement. The PDS is based on an L-type radiofrequency (RF) network, a power supply, and an inductively coupled plasma torch. However, the complexities of these technologies require an in depth understanding of the integrated components that from the PDS. A smart control system for the modified PDS was created. This novel control system aims to make the characterization process deterministic: by automating the tuning of critical electrical components in the RF network, which is achieved by the use of in-line metrology. This paper describes the main design aspects. The PDS was tested with a good correlation between capacitance and RF frequencies. The robust PDS design enables a stable discharge of plasma with a low deviation of RF signals during the total 15 hours' test.